心筋症、収縮期心機能不全及びうっ血性心不全症状の治療のためのプロベネシド (2022)
Described herein are inventions directed to methods of treating a cardiac dysfunction and symptoms of cardiac dysfunction in a subject that includes administering an amount of probenecid effective to treat a symptom of cardiac dysfunction. Probenecid may be administered in at least one of an injection, orally, or transdermally. The amount of probenecid is sufficient to result in an improved performance on a standardized 6 minute walk test, an improved New York Heart Association (NYHA) classification, a lower diuretic dose requirement, a lower serum BNP levels, a normalization of serum sodium concentrations, and combinations thereof. Probenecid may be administered over a period of about 8 hours to about 24 hours. Probenecid may be used for short term treatments, i.e., less than a week, or it may be administered in a long term manner, i.e., over a period of weeks, months, or even years.